Hydrogen Sulfide Diminishes Activation of Adventitial Fibroblasts Through the Inhibition of Mitochondrial Fission. Issue 6 (2nd June 2022) - Lu, Zhao-Yang; Guo, Chun-Ling; Yang, Bin; Yao, Yao; Yang, Zhuo-Jing; Gong, Yu-Xin; Yang, Jing-Yao; Dong, Wen-Yuan; Yang, Jun; Yang, Hai-Bing; Liu, Hui-Min; Li, Bao
Abstract: Activation of adventitial fibroblasts (AFs) on vascular injury contributes to vascular remodeling. Hydrogen sulfide (H2 S), a gaseous signal molecule, modulates various cardiovascular functions. The aim of this study was to explore whether exogenous H2 S ameliorates transforming growth factor-β1 (TGF-β1)–induced activation of AFs and, if so, to determine the underlying molecular mechanisms. Immunofluorescent staining and western blot were used to determine the expression of collagen I and α-smooth muscle actin. The proliferation and migration of AFs were performed by using cell counting Kit-8 and transwell assay, respectively. The mitochondrial morphology was assessed by using MitoTracker Red staining. The activation of signaling pathway was evaluated by western blot. The mitochondrial reactive oxygen species and mitochondrial membrane potential were determined by MitoSOX and JC-1 (5, 5′, 6, 6′-tetrachloro-1, 1, 3, 3′-tetraethylbenzimidazolyl carbocyanine iodide) staining. Our study demonstrated exogenous H2 S treatment dramatically suppressed TGF-β1–induced AF proliferation, migration, and phenotypic transition by blockage of dynamin-related protein 1 (Drp1)–mediated mitochondrial fission and regulated mitochondrial reactive oxygen species generation. Moreover, exogenous H2 S reversed TGF-β1–induced mitochondrial fission and AF activation by modulating Rho-associated protein kinase 1–dependent phosphorylation of Drp1. In conclusion, our results suggested that exogenous H2 S attenuates TGF-β1–induced AF activation through suppression of Drp1-mediated mitochondrial fission in a Rho-associated protein kinase 1–dependent fashion.